Preparation method, product and application of metal-doped cobalt-based oxide material

The metal-doped cobalt-based oxide material was prepared by solvothermal method and the nanosphere structure was formed by high-temperature calcination, which solved the problems of poor activity of existing catalysts and complex preparation process, and achieved the efficient and environmentally friendly electrocatalytic nitrate reduction and synthesis of ammonia.

CN119750659APending Publication Date: 2025-04-04ZHEJIANG NORMAL UNIV

Patent Information

Application Number
CN202411786684.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing catalysts for electrocatalyzing nitrate reduction and synthesis of ammonia have problems such as poor activity, poor product selectivity, poor stability and complex preparation process.

Method used

The metal nitrate was reacted after dissolving glycerin and isopropanol by solvothermal method to obtain a metal-doped cobalt-based oxide material, and a rough surface nanosphere structure was obtained by calcining at high temperature.

Benefits of technology

A simple, low-cost and environmentally friendly metal-doped cobalt-based oxide material is achieved, and as an electrocatalyst, it exhibits high ammonia yield, Faraday efficiency and excellent cycling performance in electrocatalytic nitrate reduction synthesis of ammonia.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750659A_ABST
    Figure CN119750659A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a metal-doped cobalt-based oxide material, which comprises the following steps: metal nitrate is dissolved in glycerol and isopropanol, a solvothermal method is adopted for reaction to obtain a reaction product, the metal in the metal nitrate comprises cobalt and at least one of nickel, copper, iron or molybdenum, the concentration of cobalt nitrate in the dissolved solution is 0.001-0.05 mM, and the concentration of cobalt nitrate in the solution is 0.01-0.05 mM; the concentration of metal nitrate except cobalt is 0.1-1 mu M; the reaction product is subjected to high-temperature calcination, the metal-doped cobalt-based oxide material with the microstructure being nanospheres with rough surfaces is obtained, the reaction temperature of the solvothermal method is 120-180 DEG C, and the reaction time is 3-6 h. The invention also discloses the metal element doped cobalt-based oxide material obtained by the preparation method and application of the metal element doped cobalt-based oxide material in electrocatalytic nitrate reduction synthesis of ammonia. The preparation method provided by the invention is simple, and the prepared metal-doped cobalt-based oxide material shows excellent electrochemical performance when applied to electrocatalytic nitrate reduction synthesis of ammonia.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the application field of cathode materials for synthesizing ammonia by electrocatalytic nitrate reduction and the preparation technology of metal-doped metal oxides, and specifically relates to a preparation method, product and application of a metal-doped cobalt-based oxide material. Background Art

[0002] Ammonia (NH3), as an indispensable chemical raw material and a new generation of carbon-free energy carrier, has attracted widespread attention in the fields of fertilizers, food, pharmaceuticals, renewable energy, etc. The synthesis of NH3 in industry is mainly dominated by the Haber-Bosch process, in which nitrogen (N2) and high-purity hydrogen (H2) gases react to produce NH3 under high temperature and pressure in the presence of an iron-based catalyst. However, the Haber-Bosch method often leads to high energy consumption and serious green greenhouse effect. Therefore, there is an urgent need to develop a green, sustainable and efficient NH3 synthesis pathway. The electrochemical synthesis of NH3 is also considered to be a new economic system for the artificial "nitrogen cycle" of green and low-carbon nitrogen-containing chemicals. However, one of the biggest challenges facing the electrocatalytic NO3RR is the sluggish reaction kinetics because it involves a complex eight-electron transfer pathway. In addition, compared with NO3 − The competition with the five-electron reduction to N2 and the inevitable HER process in aqueous solution greatly suppress the electrocatalytic efficiency.

[0003] In view of the characteristics of abundant copper, low cost, high affinity for nitrate and low toxicity, copper-based catalysts have been widely used for electrocatalytic nitrate reduction. In addition, iron-based catalysts are regarded as promising catalysts for nitrate removal due to their advantages such as non-toxicity and low cost. However, current catalysts are still limited by problems such as poor activity, poor product selectivity and poor stability. For example, a Chinese patent with publication number CN116288486A discloses a carbon cloth-supported cobalt-doped nickel phosphide electrode and its application in electrocatalytic reduction of nitrate to produce ammonia, wherein the pretreated carbon cloth is immersed in an aqueous solution containing nickel nitrate and cobalt nitrate, and a carbon cloth-supported cobalt-doped nickel hydroxide precursor is prepared by a simple hydrothermal reaction, and then phosphated in a tubular furnace; however, there are the following disadvantages: the process is complicated, the carbon cloth is fragile, and toxic gas PH3 is generated. For example, a Chinese patent with publication number CN118166386A discloses a catalyst for electrocatalytic nitrate reduction to synthesize ammonia, comprising a conductive substrate and a metal component loaded on the surface of the conductive substrate; the metal component comprises Co element and M element; the M element is selected from at least one of Cu element, Ni element, Fe element, and Ag element; the catalyst has a sheet structure self-supported by the conductive substrate; but there are the following disadvantages: the catalyst component is single and limited to alloys.

[0004] Therefore, how to further design an electrocatalyst that is easy to prepare and has high activity for nitrate reduction to ammonia remains a hot research topic in this direction. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a metal-doped cobalt-based oxide material. The preparation method is simple, and the prepared metal-doped cobalt-based oxide material exhibits excellent electrochemical performance when used in electrocatalytic nitrate reduction to synthesize ammonia.

[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is as follows: A method for preparing a metal-doped cobalt-based oxide material, the preparation method comprising the following steps: (1) dissolving a metal nitrate in glycerol and isopropanol and reacting the mixture by a solvothermal method to obtain a reaction product, wherein the metal in the metal nitrate comprises cobalt and at least one of nickel, copper, iron or molybdenum; (2) calcining the reaction product of step (1) at a high temperature to obtain a metal-doped cobalt-based oxide material having a rough surface nanosphere microstructure; In step (1), the concentration of cobalt nitrate in the dissolved solution is 0.001-0.05 mM, and the concentration of metal nitrates other than cobalt is 0.1-1 μM; In step (1), the solvothermal reaction temperature is 120-180°C and the reaction time is 3-6 h.

[0007] In step (1), preferably, the volume of glycerol is 2-8 mL, and the volume of isopropanol is 20-40 mL.

[0008] In step (1), preferably, the solvothermal reaction temperature is 140-160 °C.

[0009] In step (2), 5-10 °C min −1 The sintered steel is heated to 450-600°C at a rate of 100°C for high temperature calcination.

[0010] The present invention controls the loading amount and metal doping amount of the final sample by regulating the concentration of the electrolyte, the reaction temperature and the time, thereby achieving the regulation of the performance of the electrochemical synthesis of ammonia.

[0011] Preferably, the preparation method comprises: using 0.26 mmol of cobalt nitrate hexahydrate, 8.6 μmol of nickel nitrate nonahydrate / copper nitrate trihydrate / iron nitrate nonahydrate / molybdenum nitrate pentahydrate as reaction raw materials, 5-8 mL of glycerol and 30 mL of isopropanol as solvents, the solvothermal reaction temperature is 140-160°C, and the high-temperature calcination temperature is 450-600°C.

[0012] The present invention also provides a metal-doped cobalt-based oxide material obtained by the above preparation method.

[0013] The chemical composition of the metal-doped cobalt-based oxide material prepared by the present invention is M-Co3O4 (M=Ni, Cu, Fe, Mo, etc.). Preferably, the metal-doped cobalt-based oxide material is Ni-Co3O4, Cu-Co3O4 or Fe-Co3O4. The metal-doped cobalt-based oxide material exhibits better Faradaic efficiency and ammonia yield in the electrocatalytic nitrate reduction synthesis of ammonia.

[0014] The microscopic morphology of the metal-doped cobalt-based oxide material is a nanosphere with a rough surface and a particle size of about 300-370 nm.

[0015] The present invention also provides an application of the metal-doped cobalt-based oxide material in electrocatalytic nitrate reduction to synthesize ammonia. The metal-doped cobalt-based oxide material is used as a cathode.

[0016] Specifically, the metal-doped cobalt-based oxide material is used to electrocatalyze the reduction of nitrate to synthesize ammonia, and the metal-doped cobalt-based oxide material is used as a cathode, K2SO4 (such as a concentration of 0.1 M) and KNO3 (such as a concentration of 0.1 M) electrolytes, and Nafion 117 is used as a diaphragm to assemble an H-type electrolytic cell.

[0017] The beneficial effects of the present invention are embodied in: (1) The preparation method provided by the present invention is low-cost, environmentally friendly, requires little equipment investment, and is simple and fast to operate; (2) The metal-doped cobalt-based oxide material prepared by the present invention is used as a cathode for electrocatalytic nitrate reduction to synthesize ammonia. It has a strong adsorption effect on nitrate and can better activate nitrate. At the same time, it can inhibit the occurrence of side reactions, namely, the hydrogen evolution reaction, and exhibit good electrochemical properties, such as high ammonia yield, high Faraday efficiency and excellent cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is an XRD pattern of the nickel-doped cobalt-based oxide material prepared in Example 1 measured by a D8 X-ray diffractometer of Bruker Corporation, USA, wherein: the abscissa X is the diffraction angle (2θ), and the ordinate Y is the relative diffraction intensity; Figure 2 This is a morphology of the nickel-doped cobalt-based oxide material prepared in Example 1 observed by a Hitachi S-4800 field emission scanning electron microscope (FE-SEM); Figure 3 It is the linear voltammetric test curve of the nickel-doped cobalt-based oxide material prepared in Example 1 in 0.1 M K2SO4 + 0.1 M KNO3 tested by Shanghai Chenhua Company CHI 660E electrochemical workstation; Figure 4 The ammonia yield and Faraday efficiency of the nickel-doped cobalt-based oxide material prepared in Example 1 were tested by Shanghai Chenhua Company CHI 660E electrochemical workstation in 0.1 M K2SO4 + 0.1 M KNO3 under a series of potentials; Figure 5 The cobalt-based oxide material prepared in Comparative Example 1 was tested by a Shanghai Chenhua Company CHI 660E electrochemical workstation to measure the ammonia yield and Faraday efficiency under a series of potentials in 0.1 M K2SO4 + 0.1 M KNO3; Figure 6 The copper-doped cobalt-based oxide material prepared in Example 2 was tested by a Shanghai Chenhua Company CHI 660E electrochemical workstation to measure the ammonia yield and Faraday efficiency under a series of potentials in 0.1 M K2SO4 + 0.1 M KNO3; Figure 7 The ammonia yield and Faraday efficiency of the iron-doped cobalt-based oxide material prepared in Example 3 were tested by a Shanghai Chenhua Company CHI 660E electrochemical workstation in 0.1 M K2SO4 + 0.1 M KNO3 under a series of potentials; Figure 8 The molybdenum-doped cobalt-based oxide material prepared in Example 4 was tested by a Shanghai Chenhua Company CHI 660E electrochemical workstation to measure the ammonia yield and Faraday efficiency under a series of potentials in 0.1 M K2SO4 + 0.1 M KNO3; Fig. 9 The ammonia yield and Faraday efficiency of the nickel-doped cobalt-based oxide material prepared in Example 5 were tested by Shanghai Chenhua Company CHI 660E electrochemical workstation in 0.1 M K2SO4 + 0.1 M KNO3 under a series of potentials; Fig.10 The ammonia yield and Faraday efficiency of the nickel-doped cobalt-based oxide material prepared in Example 6 were tested by Shanghai Chenhua Company CHI 660E electrochemical workstation in 0.1 M K2SO4 + 0.1 M KNO3 under a series of potentials; Fig.11 This is a morphology image of the nickel-doped cobalt-based oxide material prepared in Comparative Example 2; Fig.12 This is a morphology image of the nickel-doped cobalt-based oxide material prepared in Comparative Example 3; Fig.13 This is the morphology of the nickel-doped cobalt-based oxide material prepared in Comparative Example 4. DETAILED DESCRIPTION

[0019] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention.

[0020] Example 1

[0021] (1) Use 0.26 mmol of cobalt nitrate hexahydrate and 8.6 μmol of nickel nitrate nonahydrate as reaction materials, 5 mL of glycerol and 30 mL of isopropanol as solvents to carry out the subsequent reaction; (2) Using a solvothermal method, the above solution was transferred to a Teflon-lined reactor, reacted at 160°C for 5 h, washed with anhydrous ethanol for multiple times, and dried in a vacuum at 80°C; (3) The powder obtained in step (2) was heated in a tube furnace at 5 °C min in an air atmosphere. −1 The mixture was heated to 450°C at a rate of 1000 ℃ and kept at that temperature for 3 hours to obtain Ni-Co3O4.

[0022] Comparative Example 1 (1) Use 0.26 mmol of cobalt nitrate hexahydrate as the reaction raw material, 5 mL of glycerol and 30 mL of isopropanol as the solvent to carry out the subsequent reaction; (2) Using a solvothermal method, the above solution was transferred to a Teflon-lined reactor, reacted at 160°C for 5 h, washed with anhydrous ethanol for multiple times, and dried in a vacuum at 80°C; (3) The powder obtained in step (2) was heated in a tube furnace at 5 °C min in an air atmosphere. −1 Heat to 450°C at a rate of 100°C and keep warm for 3 hours; The morphology of the comparative example is nanospheres with rough surfaces and a particle size of about 330 nm.

[0023] Example 2

[0024] (1) Use 0.26 mmol of cobalt nitrate hexahydrate and 8.6 μmol of copper nitrate trihydrate as reaction materials, 5 mL of glycerol and 30 mL of isopropanol as solvents to carry out the subsequent reaction; (2) Using a solvothermal method, the above solution was transferred to a Teflon-lined reactor, reacted at 160°C for 5 h, washed with anhydrous ethanol for multiple times, and dried in a vacuum at 80°C; (3) The powder obtained in step (2) was heated in a tube furnace at 5 °C min in an air atmosphere. −1 The temperature was heated to 450°C at a rate of 1.5 °C and kept at this temperature for 3 h to obtain Cu-Co3O4; The morphology of this embodiment is nanospheres with rough surfaces and a particle size of about 350 nm.

[0025] Example 3

[0026] (1) Use 0.26 mmol of cobalt nitrate hexahydrate and 8.6 μmol of ferric nitrate nonahydrate as the reaction materials, 5 mL of glycerol and 30 mL of isopropanol as the solvents for the subsequent reaction; (2) Using a solvothermal method, the above solution was transferred to a Teflon-lined reactor, reacted at 140°C for 5 h, washed with anhydrous ethanol for multiple times, and dried in a vacuum oven at 80°C; (3) The powder obtained in step (2) was heated in a tube furnace at 5 °C min in an air atmosphere. −1 The temperature was heated to 450°C at a rate of 100 °C and kept at this temperature for 3 h to obtain Fe-Co3O4; The morphology of this embodiment is nanospheres with rough surfaces and a particle size of about 350 nm.

[0027] Example 4

[0028] (1) Use 0.26 mmol of cobalt nitrate hexahydrate and 8.6 μmol of molybdenum nitrate pentahydrate as the reaction materials, 5 mL of glycerol and 30 mL of isopropanol as the solvents for the subsequent reaction; (2) Using a solvothermal method, the above solution was transferred to a Teflon-lined reactor, reacted at 160°C for 10 h, washed with anhydrous ethanol for multiple times, and dried in a vacuum oven at 80°C; (3) The powder obtained in step (2) was heated in a tube furnace at 5 °C min in an air atmosphere. −1 The temperature was heated to 450°C at a rate of 1.5°C and kept at this temperature for 3 hours to obtain Mo-Co3O4; The morphology of this embodiment is nanospheres with rough surfaces and a particle size of about 350 nm.

[0029] Example 5

[0030] (1) Use 0.26 mmol of cobalt nitrate hexahydrate and 8.6 μmol of nickel nitrate nonahydrate as reaction materials, 8 mL of glycerol and 30 mL of isopropanol as solvents to carry out the subsequent reaction; (2) Using a solvothermal method, the above solution was transferred to a Teflon-lined reactor, reacted at 160°C for 5 h, washed with anhydrous ethanol for multiple times, and dried in a vacuum at 80°C; (3) The powder obtained in step (2) was heated in a tube furnace at 10 °C min in an air atmosphere. −1 The mixture was heated to 450°C at a rate of 1000 ℃ and kept at that temperature for 3 hours to obtain Ni-Co3O4.

[0031] Example 6

[0032] (1) Use 0.26 mmol of cobalt nitrate hexahydrate and 8.6 μmol of nickel nitrate nonahydrate as reaction materials, 8 mL of glycerol and 30 mL of isopropanol as solvents to carry out the subsequent reaction; (2) Using a solvothermal method, the above solution was transferred to a Teflon-lined reactor, reacted at 160°C for 5 h, washed with anhydrous ethanol for multiple times, and dried in a vacuum at 80°C; (3) The powder obtained in step (2) was heated in a tube furnace at 5 °C min in an air atmosphere. −1 The mixture was heated to 600°C at a rate of 100 °C and kept at that temperature for 3 h to obtain Ni-Co3O4.

[0033] Comparative Example 2 The subsequent reaction was carried out using 0.283 mmol of cobalt nitrate hexahydrate and 8.1 mol of nickel nitrate nonahydrate as the reaction raw materials and 35 mL of ultrapure water plus ethylene glycol (1:1) as the solvent; The above solution was transferred to a Teflon-lined reactor by a solvothermal method, reacted at 120 °C for 5 h, washed with anhydrous ethanol for multiple times, and dried in a vacuum at 80 °C; In an air atmosphere, the powder obtained in step (2) was heated in a tube furnace at a rate of 5 °C min−1 to 450 °C and kept at this temperature for 3 h to obtain Ni-Co3O4; The morphology of the comparative example is characterized by rough surface nanorods, such as Fig.11 shown.

[0034] Comparative Example 3 (1) Use 3.5 mmol of cobalt nitrate hexahydrate and 100 μmol of nickel nitrate nonahydrate as the reaction materials, 5 mL of glycerol and 30 mL of isopropanol as the solvents for the subsequent reaction; (2) Using a solvothermal method, the above solution was transferred to a Teflon-lined reactor, reacted at 100°C for 5 h, washed with anhydrous ethanol for multiple times, and dried under vacuum at 80°C; (3) The powder obtained in step (2) was heated in a tube furnace at 5 °C min in an air atmosphere. −1 The temperature was heated to 450°C at a rate of 1.5°C and kept at this temperature for 3 hours to obtain Ni-Co3O4; The morphology of the comparative example is nanosheets, such as Fig.12 shown.

[0035] Comparative Example 4 (1) Using 0.283 mmol of cobalt nitrate hexahydrate and 8.6 mol of nickel nitrate nonahydrate as the reaction materials, 5 mL of glycerol, 5 mL of ultrapure water and 25% propylene glycol as the solvent, the subsequent reaction was carried out; (2) Using a solvothermal method, the above solution was transferred to a Teflon-lined reactor, reacted at 120°C for 5 h, washed with anhydrous ethanol for multiple times, and dried in a vacuum oven at 80°C; (3) In an air atmosphere, the powder obtained in step (2) was heated in a tube furnace at a rate of 5 °C min−1 to 450 °C and kept at this temperature for 3 h to obtain Ni-Co3O4; The morphology of the comparative example is irregular. Fig.13 shown.

[0036] Application Examples

[0037] For the performance analysis of the metal-doped cobalt-based oxides prepared in Examples 1-6 and the cobalt-based oxides prepared in Comparative Example 1, 5 mg of the powder was added with 480 μL of deionized water, 480 μL of anhydrous ethanol and 40 μL of Nafion solution, and ultrasonically dispersed uniformly. 2 The size of the electrode was evenly spread on carbon paper as the working electrode, the silver / silver chloride electrode was the reference electrode, the platinum sheet was the counter electrode, 0.1 M K2SO4 + 0.1M KNO3 was the cathode electrolyte, and 0.1 M K2SO4 was the anode electrolyte. It was placed in an H-type electrolytic cell and a series of electrochemical performance tests were carried out. After two hours of chronoamperometry test, the cathode electrolyte was taken and the ammonia content in the solution was tested by the indophenol blue method, thereby calculating the ammonia yield.

[0038] Electrochemical performance tests were performed between -0.3 and -0.9 V vs. RHE. Figure 3 The linear voltammetric test curve of the nickel-doped cobalt-based oxide prepared in Example 1 at 0~-1 V vs. RHE is shown. The difference in current of the linear voltammetric test curve of the material in the presence or absence of nitrate solution indicates that it has electrocatalytic reduction characteristics.

[0039] Figure 4-10 The electrolytic cell system assembled with the metal-doped cobalt-based oxides prepared in Examples 1-6 and the cobalt-based oxide prepared in Comparative Example 1 was tested by chronoamperometry at a series of potentials. The final ammonia yield and Faraday efficiency were calculated by characterizing the ammonium radicals in the cathode electrolyte. Among them, the nickel-doped cobalt-based oxide material prepared in Example 1 had the best performance: the ammonia yield could reach 18.77 mg h at -0.9 V vs. RHE. −1 mg −1At -0.7 V vs. RHE, the Faradaic efficiency reaches 91.17%, and at -0.7 V vs. RHE, the Faradaic efficiency is always maintained above 90% during cyclic electrocatalytic nitrate reduction for 20 h; the nickel-doped cobalt-based oxide prepared by the method of the present invention has excellent electrochemical performance for electrocatalytic nitrate reduction to synthesize ammonia.

[0040] The specific implementation methods described above provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above is only the most preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, supplements and equivalent substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a metal-doped cobalt-based oxide material, characterized in that: The preparation method comprises the following steps: (1) dissolving a metal nitrate in glycerol and isopropanol and reacting the mixture by a solvothermal method to obtain a reaction product, wherein the metal in the metal nitrate comprises cobalt and at least one of nickel, copper, iron or molybdenum; (2) calcining the reaction product of step (1) at a high temperature to obtain a metal-doped cobalt-based oxide material having a nanosphere microstructure; In step (1), the concentration of cobalt nitrate in the dissolved solution is 0.001-0.05 mM, and the concentration of metal nitrates other than cobalt is 0.1-1 μM; In step (1), the solvothermal reaction temperature is 120-180°C and the reaction time is 3-6 h.

2. The method for preparing the metal-doped cobalt-based oxide material according to claim 1, characterized in that: The solvent thermal reaction temperature is 140-160°C.

3. The method for preparing the metal-doped cobalt-based oxide material according to claim 1, characterized in that: In step (2), 5-10 °C min −1 The sintered steel is heated to 450-600°C at a rate of 100°C for high temperature calcination.

4. A metal-doped cobalt-based oxide material obtained by the preparation method according to any one of claims 1 to 3, characterized in that: The composition of the metal-doped cobalt-based oxide material is M-Co3O4, where M=Ni, Cu, Fe or Mo.

5. The metal-doped cobalt-based oxide material according to claim 4, characterized in that: The microscopic morphology of the metal-doped cobalt-based oxide material is a nanosphere with a rough surface and a particle size of about 300-370 nm.

6. The metal-doped cobalt-based oxide material according to claim 5, characterized in that: The metal-doped cobalt-based oxide material is Ni-Co3O4, Cu-Co3O4 or Fe-Co3O4.

7. Use of the metal-doped cobalt-based oxide material according to claim 4 in electrocatalytic nitrate reduction to synthesize ammonia.

8. The use according to claim 7, characterized in that: The metal-doped cobalt-based oxide material serves as a cathode.

Citation Information

Patent Citations

  • Carbon cloth loaded cobalt-doped nickel phosphide electrode and application thereof in preparation of ammonia by electrocatalytic reduction of nitrate

    CN116288486A

  • Catalyst for synthesizing ammonia through electrocatalytic nitrate reduction and preparation method and application thereof

    CN118166386A

Cited By

  • Electroreduction nitrate ammonia synthesis CuOx / CoOx nano material with oxygen vacancy defect, and preparation method and application thereof

    CN120231091A

  • Lanthanide-metal-doped cobaltosic oxide catalyst, preparation method thereof and application of lanthanide-metal-doped cobaltosic oxide catalyst in preparation of ammonia by reducing nitrate

    CN120556078A